One-step construction of saturated six-membered rings directly using calcium carbide as an acetylene source: synthesis of 1, 3, 5-triaroylcyclohexanes. Issue 29 (21st July 2016) - Li, Zheng; He, Lili; Fu, Rugang; Song, Geyang; Song, Wenli; Xie, Demeng; Yang, Jingya
Abstract: Saturated six-membered rings were constructed directly using calcium carbide as an acetylene source by one-step procedure, and functionalized cyclohexanes, 1, 3, 5-triaroylcyclohexanes, were efficiently synthesized by reactions of calcium carbide with aromatic or heteroaromatic aldehydes in high yield. This protocol has the advantages of using inexpensive and renewable resource, no flammable and explosive gas and no transition-metal catalysts. Graphical abstract: